Dual Substitution and Spark Plasma Sintering to Improve Ionic Conductivity of Garnet Li(7)La(3)Zr(2)O(12) - Dong, Zhencai (Nanomaterials (Basel), 2019)
Garnet Li(7)La(3)Zr(2)O(12) is one of the most promising solid electrolytes used for solid-state lithium batteries. However, low ionic conductivity impedes its application. Herein, we report Ta-doping garnets with compositions of Li(7-x)La(3)Zr(2-x)Ta(x)O(12) (0.1 ≤ x ≤ 0.75) obtained by solid-state reaction and free sintering, which was facilitated by graphene oxide (GO). Furthermore, to optimize Li(6.6)La(3)Zr(1.6)Ta(0.4)O(12), Mg(2+) was select as a second dopant. The dual substitution of Ta(5+) for Zr(4+) and Mg(2+) for Li(+) with a composition of Li(6.5)Mg(0.05)La(3)Zr(1.6)Ta(0.4)O(12) showed an enhanced total ionic conductivity of 6.1 × 10(−4) S cm(−1) at room temperature. Additionally, spark plasma sintering (SPS) was applied to further densify the garnets and enhance their ionic conductivities. Both SPS specimens present higher conductivities than those produced by the conventional free sintering. At room temperature, the highest ionic conductivity of Li(6.5)Mg(0.05)La(3)Zr(1.6)Ta(0.4)O(12) sintered at 1000 °C is 8.8 × 10(−4) S cm(−1), and that of Li(6.6)La(3)Zr(1.6)Ta(0.4)O(12) sintered at 1050 °C is 1.18 × 10(−3) S cm(−1).